India's Three farm Laws and the issues they exposed. (3rd April 2022) - Rai, Jasdev Singh
ABSTRACT: The complex interconnected issues, interests and factors that led the BJP Government in India to introduce the Three Farm Laws in what it claimed were progressive and subsequently repealed following the successful protests by farmers who saw them as threats to their livelihoods and culture and further resistance by states fighting off encroachment on their powers are multifaced. These include persistent political tensions in India's asymmetrical federalism, fears around livelihoods, concerns of cultural annihilation, effects of market orientated World Trade Organization rules and efforts by the CAIRN group of countries to penetrate the Indian market.